MANAGEMENT OF JOINT-STOCK COMPANIES AND FARMS BY USING FAIR VALUE OF AGRICULTURAL EQUIPMENT IN FINANCIAL STATEMENTS ON THE EXAMPLE OF IMT 533 TRACTOR - Radović, Milan; Vitomir, Jelena; Laban, Bogdan; Jovin, Slobodanka; Nastic, Sanda; Popovic, Vera; Popovic, Slobodan (Economics of Agriculture, 2019)
More demanding management requires management to foster the application of different mechanisms. One of the upcoming ways of improving management is the use of the fair value of property and equipment in the business books of the company. The authors of this study emphasize the importance of fair valuation of agricultural equipment, processing surveyed 382 legal entities of the Republic of Serbia, in the case of widespread tractor IMT 533 agricultural holdings in 207 and 175 joint-stock companies. To show the real application of fair value, the research period lasted from 2015 to 2018. We came to the basic conclusion that there is a statistically significant relationship between organizations, enterprises and the age of the tractor to the application of the fair value of the tractor in the business books of the company. There is also a conclusion that fair financial reporting brings about benefits to agricultural entities of other legal forms.